(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Stunting is a condition in which a child’s growth is stunted due to malnutrition since 1.000 First Days of Life. This condition will not only impact the child’s life, but also the country in macro scale. The more the children with stunting condition are, Gross Domestic Products will decrease due to the unproductive human resources. Indonesia is one of the countries which still has high stunting prevalence number. This condition causes the government to take on policy for overcoming stunting, one of which is through health communication programs. One of the regions in Indonesia which has successfully done the stunting prevention program so the prevalence number has decreased significantly is Trenggalek Regency. This success turns out to be encouraged by bio-power reproduction by health cadre. Therefore, in this research, bio-power reproduction by health cadre in stunting prevention health communication will be described. The used research methods are critical paradigm, qualitative research approach, with the research being descriptive. The used method in this research is specifically discourse analysis method based on Foucault concept. The result from the research shows that the forming of bio-power reproduction by health cadre is initiated with bio-politics by the government. Then, the government distributes the knowledge to health cadre, which is then re-distributed by health cadre to the targeted subjects. Health cadre figure as an authority holder who is described to have more knowledge and their suggestions are able to help society, and a figure as preventive health care agent who has autonomy- being not tending, attributed as a cadre validated by the government, and able to convey effective messages in accordance with the needs of targeted subjects also encourages bio-power reproduction. Surveillance by the cadre also becomes an important part in bio-power reproduction. The result from bio-power reproduction can be seen from the similarity of the understanding about stunting, its causes, and how to prevent it, and the change of the behaviors of the targeted subjects. The obstacles for bio-power reproduction come from within the targeted subjects such as the wrong assumptions, unwillingness to interact, and personal inconvenience, and external factors such as improper information from mass media and social media.